2017
DOI: 10.4238/gmr16019280
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis and identification of SSR markers associated with rice blast disease in a BC<sub>2</sub>F<sub>1</sub> backcross population

Abstract: ABSTRACT. Rice (Oryza sativa L.) blast disease is one of the most destructive rice diseases in the world. The fungal pathogen, Magnaporthe oryzae, is the causal agent of rice blast disease. Development of 2 N. Hasan et al. Genetics and Molecular Research 16 (1): gmr16019280 resistant cultivars is the most preferred method to achieve sustainable rice production. However, the effectiveness of resistant cultivars is hindered by the genetic plasticity of the pathogen genome. Therefore, information on genetic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
(27 reference statements)
1
4
0
Order By: Relevance
“…An isolate of M. oryzae cannot be avirulent to the rice plant, unless the rice plant has genes that make it resistant to that isolate [24,36]. Partial resistance can be race specific [1,2,18]. The findings of this research support the research output reported by IRRI, Philippines; that is, that one or two dominant genes are present and the 'Mashuri' cultivar was susceptible (S).…”
Section: Phenotypic Screening For Blast Resistance In the Bc 2 F 1 Populationsupporting
confidence: 69%
See 4 more Smart Citations
“…An isolate of M. oryzae cannot be avirulent to the rice plant, unless the rice plant has genes that make it resistant to that isolate [24,36]. Partial resistance can be race specific [1,2,18]. The findings of this research support the research output reported by IRRI, Philippines; that is, that one or two dominant genes are present and the 'Mashuri' cultivar was susceptible (S).…”
Section: Phenotypic Screening For Blast Resistance In the Bc 2 F 1 Populationsupporting
confidence: 69%
“…MR263, a popular and high-yielding rice variety, was used as a recurrent parent with elite agronomic traits that is susceptible to blast. The BC 2 F 1 population was produced from a cross between MR263 and PS1 and genotyped with suitable SSR markers that were linked to blast resistance genes [2,5].…”
Section: Plant Materialsmentioning
confidence: 99%
See 3 more Smart Citations